Chomp - Hiaasen, Carl. (New York : Knopf, 2012)
The difficult star of the reality television show "Expedition Survival" disappears on location in the Florida Everglades, where they were filming animals from the wildlife refuge run by Wahoo Crane's family, and Wahoo and classmate Tuna Gordon set out to find him, but they must avoid Tuna's gun-happy father.
Wilson's Children, October 2012.
Wilson's Junior High School, October 2012.
School Library Journal starred, March 2012.
Library Media Connection starred, May 2012.
Publisher's Weekly, January 2012.
Booklist, November 2011.
Keywords: Reality television programs -- Juvenile fiction; Television -- Production and direction -- Juvenile fiction; Missing persons -- Juvenile fiction; Wildlife refuges -- Juvenile fiction; Reality television programs -- Fiction; Television -- Production and direction -- Fiction; Missing persons -- Fiction; Wildlife refuges -- Fiction; Adventure and adventurers -- Fiction; Reality television programs -- Fiction; Television -- Production and direction -- Fiction; Missing persons -- Fiction; Wildlife refuges -- Fiction; Adventure fiction; Reality television programs -- Fiction; Television -- Production and direction -- Fiction; Missing persons -- Fiction; Wildlife refuges -- Fiction; Everglades (Fla.) -- Juvenile fiction; Florida -- Juvenile fiction; Everglades (Fla.) -- Fiction; Florida -- Fiction; Everglades (Fla.) -- Fiction; Florida -- Fiction; Everglades (Fla.) -- Fiction; Florida -- Fiction; Adventure fiction